Activation of Protein Kinase A Contributes to the Expression But Not the Induction of Long-Term Hyperexcitability Caused by Axotomy ofAplysia Sensory Neurons - Liao, Xiaogang (J Neurosci, 1999)
Nociceptive sensory neurons (SNs) in Aplysia provide useful models to study both memory and adaptive responses to nerve injury. Induction of long-term memory in many species, includingAplysia, is thought to depend on activation of cAMP-dependent protein kinase (PKA). Because Aplysia SNs display similar alterations in models of memory and after nerve injury, a plausible hypothesis is that axotomy triggers memory-like modifications by activating PKA in damaged axons. The present study disproves this hypothesis. SN axotomy was produced by (1) dissociation of somata from the ganglion [which is shown to induce long-term hyperexcitability (LTH)], (2) transection of neurites of dissociated SNs growing in vitro, or (3) peripheral nerve crush. Application of the competitive PKA inhibitor Rp-8-CPT-cAMPS at the time of axotomy failed to alter the induction of LTH by each form of axotomy, although the inhibitor antagonized hyperexcitability produced by 5-HT application. Strong activation of PKA in the nerve by coapplication of a membrane-permeant analog of cAMP and a phosphodiesterase inhibitor was not sufficient to induce LTH of either the SN somata or axons. Furthermore, nerve crush failed to activate axonal PKA or stimulate its retrograde transport. Therefore, PKA activation plays little if any role in the induction of LTH by axotomy. However, the expression of LTH was reduced by intracellular injection of the highly specific PKA inhibitor PKI several days after nerve crush. This suggests that long-lasting activation of PKA in or near the soma contributes to the maintenance of long-term modifications produced by nerve injury.